Parametric studies on the storage stability and aging effect of biodiesel treated with Eucalyptus oil as a cost‐effective green‐antioxidant additive. (23rd August 2020) - Yatish, K. V.; Lalithamba, H. S.; Sakar, M.; Balakrishna, Geetha R.; Omkaresh, B. R.; Arun, S. B.
Summary: Oxidation stability is one of the most significant fuel quality standards for biodiesel and mainly distresses the stability of biodiesel. Therefore, the present work aims to report the Eucalyptus oil (EO) as a natural green antioxidant additive to evaluate the oxidation stability of biodiesel produced from dairy waste scum, Bauhinia variegata and Butea monosperma oil. The obtained results have also been compared with the conventional synthetic antioxidant, butylated hydroxy toluene (BHT). The oxidation stability of the biodiesel treated with these additives was evaluated using the professional biodiesel Rancimat instrument. Further, the fuel properties kinematic viscosity and acid value were measured during the storage period. The obtained results showed an increase in the induction period in the biodiesel sample treated with EO, indicating a protective effect and inhibiting the oxidation initiation step. As a result, the oxidation stability of dairy waste scum methyl ester (DWSME), B variegata methyl ester (BVME) and B monosperma methyl ester (BMME) was found to be 10, 8 and 8 hours, respectively, during 90 days storage when the natural antioxidant EO with a concentration of 4000 ppm was used and these obtained values were in the limit of EN 14214 standard. Interestingly, these values were found to be on par with the oxidation stability of DWSME ( 11 hours), BVME ( 9 hours) and BMME ( 9 hours), when the synthetic antioxidant BHT was used with a concentration of 3000 ppm during the 90 days storage. Although the addition of EO as antioxidant resulted in increase in kinematic viscosity and acid value of the biodiesel samples, those values well‐fall in the ASTM 6751 standard limit. On the other hand, synthetic antioxidant BHT showed enhanced results as compared to the EO. However, the effectiveness of the proposed natural antioxidant additive (EO) is on par with the synthetic antioxidant (BHT), which can be replaced for cost‐effectiveness, non‐toxic and safer consumption of biodiesel as compared to synthetic antioxidant‐treated biodiesel. Abstract : This study reports the Eucalyptus oil as a natural green‐antioxidant additive to improve the oxidation stability of biodiesel produced from various feedstocks. Results showed an increase in the induction period in Eucalyptus oil‐treated biodiesel, indicating a protective effect and inhibiting the oxidation initiation step in biodiesel. The efficiency of this natural antioxidant additive is on par to the synthetic antioxidant, which can be replaced for its cost‐effectiveness, non‐toxic and safer‐consumption of biodiesel as compared to the synthetic antioxidant‐treated biodiesel.